Asuhan Keperawatan pada Bayi Ny. S dengan Masalah Berat Badan Lahir Rendah (BBLR) - Utari Ariyanti; Selvia Yolanda Dalimunthe; Yessica Hotmaida Tarihoran (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Low Birth Weight (LBW) is one of the main causes of high neonatal morbidity and mortality in Indonesia. This study aims to describe the comprehensive nursing care process for a baby with LBW in the NICU room of Bina Kasih Hospital Medan. The design used was a descriptive case study with one patient as the subject, Mrs. S, who was born weighing 1,500 grams and was 35 weeks and 4 days gestational age. Data were collected through direct observation, interviews with parents, medical record documentation studies, and literature reviews. The results of the study showed four main nursing diagnoses, namely ineffective thermoregulation, nutritional imbalance less than body requirements, risk of infection, and parental anxiety. Interventions were carried out through temperature monitoring, breastfeeding through OGT, umbilical cord care, and family education. After 3 days of care, two nursing diagnoses were successfully resolved, while the other two required follow-up. This study emphasizes the importance of a holistic and integrated nursing approach to improve clinical outcomes of LBW babies, as well as the active role of nurses in education and emotional support to families. Appropriate and evidence-based nursing care is the key to optimal neonatal care.